Coercion in the Courtroom: Unpacking the Reality of False Guilty Pleas in Canada - Leclerc, Chloé; Euvrard, Elsa; Abellan-Almenara, Meritxell (The Wrongful Conviction Law Review, 2025)
Despite a significant growth of scientific knowledge on wrongful convictions and miscarriages of justice, the phenomenon of false guilty pleas remains largely understudied in Canada. Drawing from data obtained through the responses of a questionnaire administered to 55 defendants and 11 in-depth semi-directed interviews, this article explores the profile of the individuals who enter false guilty pleas and the reasons why they do so. The context and circumstances behind false guilty pleas are ranked by their prevalence (in the survey) and describe with interviewees stories. Finally, the article discusses the perception of the person entering a false guilty plea regarding the coerciveness or voluntariness of their decision.